Postulaty de lege ferenda dotyczące ochrony prywatności użytkowników usług Over-the-Top w Unii Europejskiej - Kotecka-Kral, Sylwia (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The study discusses the issue of insufficient legal regulation of privacy protection in so-called Over-the-Top services, i.e. provided over the Internet at European Union level. It presents proposals for a postulated legal act with the rank of a regulation, which will replace Directive 2002/58 incompatible with technological realities and supplement the provisions of the GDPR in the protection of one of the fundamental rights, which is the right to privacy.
Keywords: right to privacy; privacy protection; Directive 2002/58; GDPR; personal data; electronic communications service; Over-the-Top service; interpersonal communications service